Effect of Nocturnal Oxygen Therapy on Daytime Pulmonary Hemodynamics in Patients With Chronic Obstructive Pulmonary Disease Traveling to Altitude: A Randomized Controlled Trial - Lichtblau, Mona; Latshang, Tsogyal D.; Aeschbacher, Sayaka S.; Huber, Fabienne; Scheiwiller, Philipp M.; Ulrich, Stefanie; Schneider, Simon R.; Hasler, Elisabeth D.; Furian, Michael; Bloch, Konrad E.; Saxer, Stéphanie; Ulrich, Silvia (Frontiers in Physiology, 2021)
Introduction We investigated whether nocturnal oxygen therapy (NOT) mitigates the increase of pulmonary artery pressure in patients during daytime with chronic obstructive pulmonary disease (COPD) traveling to altitude. Methods Patients with COPD living below 800 m underwent examinations at 490 m and during two sojourns at 2,048 m (with a washout period of 2 weeks < 800 m between altitude sojourns). During nights at altitude, patients received either NOT (3 L/min) or placebo (ambient air 3 L/min) via nasal cannula according to a randomized crossover design. The main outcomes were the tricuspid regurgitation pressure gradient (TRPG) measured by echocardiography on the second day at altitude (under ambient air) and various other echocardiographic measures of the right and left heart function. Patients fulfilling predefined safety criteria were withdrawn from the study. Results Twenty-three COPD patients [70% Global Initiative for Chronic Obstructive Lung Disease (GOLD) II/30% GOLD III, mean ± SD age 66 ± 5 years, FEV1 54% ± 13% predicted] were included in the per-protocol analysis. TRPG significantly increased when patients traveled to altitude (from low altitude 21.7 ± 5.2 mmHg to 2,048 m placebo 27.4 ± 7.3 mmHg and 2,048 m NOT 27.8 ± 8.3 mmHg) difference between interventions (mean difference 0.4 mmHg, 95% CI −2.1 to 3.0, p = 0.736). The tricuspid annular plane systolic excursion was significantly higher after NOT vs. placebo [2.6 ± 0.6 vs. 2.3 ± 0.4 cm, mean difference (95% confidence interval) 0.3 (0.1 − 0.5) cm, p = 0.005]. During visits to 2,048 m until 24 h after descent, eight patients (26%) using placebo and one (4%) using NOT had to be withdrawn because of altitude-related adverse health effects (p < 0.001). Conclusion In lowlanders with COPD remaining free of clinically relevant altitude-related adverse health effects, changes in daytime pulmonary hemodynamics during a stay at high altitude were trivial and not modified by NOT. Clinical Trial Registration www.ClinicalTrials.gov, identifier NCT02150590.